Ecological and health risk assessment of heavy metals in the Hattar industrial estate, Pakistan. (2nd January 2020) - Jehan, Shah; Khattak, Seema Anjum; Muhammad, Said; Ahmad, Rafiq; Farooq, Muhammad; Khan, Sardar; Khan, Abdullah; Ali, Liaqat
Abstract: This study aimed to determine the heavy metals (HMs) contaminations in soil of the Hattar industrial estate (HIE), Haripur, Khyber Pakhtunkhwa. For this purpose, various types of soils were collected in HIE and analyzed for the HMs concentrations. The HMs showed highest contamination levels in wastewater irrigated agriculture soil (WWIAS), followed by waste dump site soil (WDSS), and the lowest in range land soil (RLS). Determined HMs concentrations were used for pollution quantification factors, including contamination factors (CFs), pollution load index (PLI), ecological risk factor (ER), and potential health risk assessment, including chronic or non-cancer and cancer risk levels.